(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article analyses the literary legacy of Concepcion Arenal, one of the first feminists in Spain. Working in diverse areas, this activist and reformer made an immeasurable contribution to the struggle for a free and just society during the second half of the 19th century. The first section of the paper provides an insight into her achievements in humanitarian, criminal, and international law, as well as the prison reform, while the second part contrasts the author’s engagement in resolving the social issues of the era, the struggle for human rights, especially labour and women’s rights. Special attention is paid to Concepcion Arenal’s endeavours in the field of female emancipation in Spain, entailing primarily the right to education and work. On the selected literary corpus, which consists of her most important feminist studies: A Woman of the Future and Women’s Education, the most important postulates of early feminism in Spain are analysed through a descriptive review of the content of the texts. The importance of the Spanish author’s literary thought at that moment and its influence on the future generations of Spanish feminists are also re-examined.